2007
DOI: 10.1111/j.1365-2702.2006.01563.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ feelings and thoughts about using physical restraints on hospitalized older patients

Abstract: The findings of this study may contribute to filling the gaps in nursing knowledge, to improving protocols for physical restraint use in hospitals, and may also assist nurse managers to create a supportive practice environment. It is recommended that in-service training programmes should cover misconceptions regarding physical restraint use, ethical issues and how to cope with feelings while using physical restraints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
101
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(114 citation statements)
references
References 37 publications
7
101
1
5
Order By: Relevance
“…In such situations, their autonomy was overruled, despite the fact that there was no danger to life or health. As previous studies have shown, 4,7,12,15,16,19,28 RNs using coercive measures had convinced themselves that residents' problematic behaviour was due to lack of insight, and therefore, constraints were seen as appropriate. It seems as though legal rights were understood as actions to prevent falls or harm, and not as actions to support autonomy and non-coercive dementia care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In such situations, their autonomy was overruled, despite the fact that there was no danger to life or health. As previous studies have shown, 4,7,12,15,16,19,28 RNs using coercive measures had convinced themselves that residents' problematic behaviour was due to lack of insight, and therefore, constraints were seen as appropriate. It seems as though legal rights were understood as actions to prevent falls or harm, and not as actions to support autonomy and non-coercive dementia care.…”
Section: Discussionmentioning
confidence: 99%
“…Previous international studies have revealed similar results. 5,28,29 There was a major difference between the two nursing strategies that included coercive treatment. This difference could be related to educational skills and/or adequate staffing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States only, 8.63% of older patients in acute care hospitals were prescribed tranquilizers 53 ; the prevalence of use of physical restraints was 50 per 1000 patients' bed days. 54 However, the use of physical restraints on older patients with dementia is still highly prevalent in hospitals and is aimed to ensure the patient's safety [55][56][57] and to prevent disruption of therapy. 54 Other practices included discharge planning and allocating a separate space of the ward dedicated for the care of patients with delirium.…”
Section: Practices Used By Nursesmentioning
confidence: 99%
“…Por ejemplo, cuando se estudian las actitudes entre personal de enfermería se ve que las respuestas emocionales son variadas incluyendo tristeza y culpa, que coexisten con manifestaciones sobre la seguridad que aporta su uso 17 . Existe una ambivalencia emocional que genera conflictos, ya que la mayoría sienten pena por el anciano y tienen sentimientos negativos hacia el uso de las sujeciones a la vez que la liberación les genera dificultades.…”
unclassified